2010
DOI: 10.1016/j.neurobiolaging.2008.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ɛ4 influences on episodic recall and brain structures in aging pilots

Abstract: The apolipoprotein (APOE) ε4 allele is associated with cognitive deficits and hippocampal atrophy in nondemented middle-aged and older adults. It is not known to what extent this genetic risk factor for Alzheimer's disease (AD) impacts performance in late middle-aged and older workers in cognitively demanding occupations. This cross-sectional analysis examines brain–cognitive–genetic relationships in actively flying general aviation pilots, half of whom are APOE ε4 carriers. Fifty pilots were studied with stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
(46 reference statements)
4
26
2
Order By: Relevance
“…Together these variables predicted a significant amount of variance in episodic memory performance, R 2 = .183, p < .001. Replicating previous findings (e.g., Adamson et al, 2010; Backman et al, 2005; Bondi et al, 1995; Filippini et al, 2009; Nilsson et al, 2006; Pike et al, 2011; Schultz et al, 2008; Wisdom et al, 2011), episodic memory scores were significantly lower in older adults, β = −.367, p < .001, and in APOE ε4 carriers, β = .166, p = .015. The effect of APOE ε4 carrier status was larger in older than younger adults; however, the Age × APOE interaction was not significant, β = −.320, p = .142 (see Figure 1).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Together these variables predicted a significant amount of variance in episodic memory performance, R 2 = .183, p < .001. Replicating previous findings (e.g., Adamson et al, 2010; Backman et al, 2005; Bondi et al, 1995; Filippini et al, 2009; Nilsson et al, 2006; Pike et al, 2011; Schultz et al, 2008; Wisdom et al, 2011), episodic memory scores were significantly lower in older adults, β = −.367, p < .001, and in APOE ε4 carriers, β = .166, p = .015. The effect of APOE ε4 carrier status was larger in older than younger adults; however, the Age × APOE interaction was not significant, β = −.320, p = .142 (see Figure 1).…”
Section: Resultssupporting
confidence: 85%
“…Although no study has examined whether APOE ε4 carrier status influences everyday memory, a number of studies of memory for verbal and pictorial materials have shown that ε4 carrier status affects episodic memory in older adults (e.g., Adamson et al, 2010; Baxter, Caselli, Johnson, Reiman, & Osborne, 2003; Bondi et al, 1995; Caselli et al, 2009; Nilsson et al, 2006; Packard et al, 2007; Pike et al, 2011; Wisdom et al, 2011). APOE genotype interacts with age such that the effect of the ε4 allele is more detrimental in older adults, and is often absent Filippini et al, 2009) or even beneficial in younger adults (Alexander et al, 2007; Mondadori et al, 2007; Rusted, Evans, King, Dowell, Tabet, & Tofts, 2013).…”
mentioning
confidence: 99%
“…It is unclear whether healthy carriers of the APOEε4 variant have smaller hippocampal volumes. Several reports of negative effects of APOEε4 on the hippocampal volume in healthy participants (Chiang et al 2011; Cohen et al 2001; den Heijer et al 2012; Lind et al 2006; Lu et al 2011; Moffat et al 2000) are balanced by studies that failed to find such an association (Adamson et al 2010; Cherbuin et al 2008; Ferencz et al 2013; Hostage et al 2013; Lemaître et al 2005; Richter-Schmidinger et al 2011; Troyer et al 2012), with some finding the effect only for the homozygotes (Crivello et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Intra- and inter-rater reliability coefficients are .90 or better (Hsu et al, 2002; Schuff et al, 2009b). The SNT method has been implemented by the Alzheimer’s Disease Neuroimaging Initiative (ADNI) (Schuff et al, 2009b), and SNT has been used in our prior work showing hippocampal volume correlates with memory performance ( r = .47) (Adamson et al, 2010). SNT total hippocampal volume, which includes hippocampal gray matter only and no nearby regions such as the parahippocampal gyrus (PHG), was chosen as the a priori primary ROI.…”
Section: Methodsmentioning
confidence: 99%